2020
DOI: 10.1111/dth.14099
|View full text |Cite
|
Sign up to set email alerts
|

Serum CCL22 levels decreased in parallel with disease activity in CCR4 ‐positive mycosis fungoides treated with mogamulizumab

Abstract: Mogamulizumab is a humanized anti-CC chemokine receptor type (CCR)4 antibody that shows cytotoxicity against CCR4+ lymphoma cells via antibody-dependent cellmediated cytotoxicity in advanced cutaneous T cell lymphoma (CTCL) patients. The production levels of ligands for CCR4, that is, Chemokine (C-C motif) ligand (CCL)17 and CCL22, are important for the assessment of the disease activity in CTCL patients. We evaluated the serum levels of CCL17, CCL19, CCL22, C-X-C motif chemokine ligand (CXCL)10, and CXCL13, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Last but not least, the association between CXCL6 expression and antibody‐dependent cell‐mediated cytotoxicity of PD‐L1 antibody therapy should not be overlooked in ESCC. One piece of article (Ohuchi et al, 2020) reported that, compared with CXCL10 and CXCL13, Chemokine (C‐C motif) ligand (CCL) CCL22 may be more likely a predictor of the efficacy of antibody treatment of cutaneous T cell lymphoma. Suggested by the study, the potential significance of CXCL6 in ESCC treated with anti‐PD‐L1 mono‐antibody therapy remains unclear that left to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, the association between CXCL6 expression and antibody‐dependent cell‐mediated cytotoxicity of PD‐L1 antibody therapy should not be overlooked in ESCC. One piece of article (Ohuchi et al, 2020) reported that, compared with CXCL10 and CXCL13, Chemokine (C‐C motif) ligand (CCL) CCL22 may be more likely a predictor of the efficacy of antibody treatment of cutaneous T cell lymphoma. Suggested by the study, the potential significance of CXCL6 in ESCC treated with anti‐PD‐L1 mono‐antibody therapy remains unclear that left to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…This activity might be explained by previous preclinical studies that focused on TAMs [ 12 , 22 , 25 ]. Since serum CCL22 levels represent disease activity in patients with early- and advanced-stage MF [ 12 , 25 ], and the production of CCL22 from TAMs is suppressed by topical 5% IQM in vivo (in a B16F10 mouse melanoma model) [ 22 ], the administration of topical 5% IQM may decrease serum CCL22 levels, leading to the suppression of tumor progression in patients with advanced-stage MF. Since the case series of advanced-stage MF treated with topical 5% IQM are limited, further case series will be needed to prove the efficacy of IQM.…”
Section: Topical Formulation Options For Ctclsmentioning
confidence: 97%
“…Overall median times to response were 3.3 months (IQR 2.0–6.4) in the mogamulizumab group and 5.1 months (2.9–8.5) in the vorinostat group. The most common treatment-related AEs in the mogamulizumab group were infusion reaction (32%), drug eruption (20%), diarrhea (23%), and fatigue (22%) [ 25 ]. In addition, the major SAEs by mogamulizumab were pyrexia (4%) and cellulitis (3%), suggesting that mogamulizumab is a well-tolerated systemic therapy for advanced CTCL [ 26 ].…”
Section: Systemic Treatment Options For Advanced Ctclsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, increased serum CCL22 levels reflect the increased activity of TAMs and tumor progression to more advanced stage.These results were in agreement with Tanita et al14 who reported that serum levels of CCL22 significantly increased in advanced CTCL compared with CTCL. Also, Ohuchi et al32 concluded that the production levels of CCL22 are important for the assessment of the disease activity in CTCL patients.To our knowledge, the current work is the first to correlate serum CCL22 levels with dermal TAMs in MF and SS patients, our results revealed that serum CCL22 levels were significantly positively correlated with dermal CD68+ and CD163+ TAMs count as well as CD163/CD68 ratio. Also, the correlation between sCD163 and CCL22 serum levels showed a significant positive correlation.As CCL22 is a chemokine specifically released by M2 macrophages, their high levels in tumor stage MF and SS indicate that most TAMs within the TME have been polarized to M2-type TAMs (CD163 + TAMs).…”
mentioning
confidence: 99%